2019
DOI: 10.1161/strokeaha.119.026362
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Magnetic Resonance Imaging of Cervicocranial Artery Dissection

Abstract: Background and Purpose— We aimed to systematically investigate the characteristics of cervicocranial artery dissection (CCAD) on high-resolution magnetic resonance imaging that are associated with acute ischemic stroke. Methods— Patients with CCAD were recruited and divided into stroke and nonstroke groups. The lesion location, the presence of a double lumen, intimal flap, intramural hematoma, pseudoaneurysm, irregular surface, intraluminal thrombus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 38 publications
2
59
1
Order By: Relevance
“…After full-text reviews of these 19 articles, eight were excluded because they contained insufficient information in terms of the proportion of image findings of acute to subacute craniocervical AD on MR-VWI ( 2 , 5 , 6 , 23 27 ) and one because of suspected population overlap ( 28 ). Finally, 11 articles were included in the final analysis ( 4 , 7 15 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…After full-text reviews of these 19 articles, eight were excluded because they contained insufficient information in terms of the proportion of image findings of acute to subacute craniocervical AD on MR-VWI ( 2 , 5 , 6 , 23 27 ) and one because of suspected population overlap ( 28 ). Finally, 11 articles were included in the final analysis ( 4 , 7 15 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Artery dissection implies a tear in the wall of an artery, leading to intrusion of blood within the layers of arterial walls. An important pathological feature of symptomatic cervicocranial artery dissection is that the affected vessel wall becomes the nidus for distal embolization [16]. Different patterns of disruption of the endothelium, intima, and internal elastic lamina can result in an influx of circulating blood into the vessel wall layers.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Different patterns of intimal injury in IADs have been reported [13,15]. Previous studies reported that surface irregularity and intraluminal thrombus are independently related to stroke occurrence in patients with cervicocranial artery dissection and that the shape of carotid plaque is significantly associated with the presence of intraplaque hemorrhage [16,17]. We hypothesized that different shapes of IMH, according to the proximal and distal position of the hematoma, alter hemodynamics and have different clinical presentations.…”
Section: Introductionmentioning
confidence: 93%
“…Typical radiological features can be visualized with MRI, MRA, and CTA (case 1) as they are sensitive to detect intramural hematoma; however, some cases, especially intracranial VAD, will need confirmation by conventional angiography (case 2), if noninvasive techniques were not conclusive [12]. Recently, high-resolution MRI (HR-MRI) has been reported to offer the advantage of direct visualization both of vessel wall abnormalities and an intraluminal thrombus; however, most patients do not have access to such techniques [13].…”
Section: Discussionmentioning
confidence: 99%